When bone marrow is Silent: PET/CT detection of splenic lymphoma in persistent pancytopenia - Aslam, Shazia; Sajid, Aitzaz; Riaz, Alina; Fatima, Zarfeen; Rafaqat, Laiba (International Journal of Pathology, 2026)
Background: Chronic pancytopenia in adults presents a broad differential diagnosis and often requires comprehensive evaluation to identify the underlying etiology. Case Report: We present the case of a middle-aged man whose initial tests, which included a trephine biopsy and bone marrow aspiration, failed to reveal the cause of his persistent pancytopenia, hepatosplenomegaly, and constitutional symptoms. No cause was found after extensive testing for infections, autoimmune diseases, and dietary deficiencies. Eventually, ^18F-FDG PET/CT showed that the spleen was diffusely hypermetabolic, which led to the suspicion that the patient had primary splenic lymphoma. Histopathological analysis and splenectomy confirmed the diagnosis. The patient unfortunately passed away before treatment could be initiated. Conclusion: This case study demonstrates the limitations of traditional marrow-based diagnostics in some hematologic malignancies and emphasizes the critical need for sophisticated imaging, specifically PET/CT, in detecting hidden lymphomas when regular investigations provide inconclusive results.